Centro cultural y biblioteca - Jiménez Hurtado, Carlos; Palacios González, Juan A; Parrado Redondo, Juan; Riofrío Fadrique, Miguel; Sanroma Simal, Jesús (Informes de la Construcción, 1985)
No disponible.